2003
DOI: 10.1007/s11745-003-1497-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolar lipid composition ofChenopodium albumgrown in continuously cultivated and nondisturbed soils

Abstract: Chenopodium album L. plants grown in continuously cultivated and in nondisturbed soils were compared in terms of the compositions of nonpolar extracts of the corresponding aerial parts. Both light petroleum ether extracts of C. album L. were analyzed by high-performance thin-layer LC, capillary GC, and capillary GC-EI-MS. Further percolation and medium-pressure LC, along with EI-MS analysis, permitted the separation and identification of the chemical constituents. Differences were observed between mean content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Induced resistance is defined as changes in plant chemistry or physiology with measurable effect on herbivore performance via behavior or biology (1). Results previously reported by our laboratory showed that different kinds of environmental stresses could affect secondary metabolite production, quinolizidine alkaloids among them (2)(3)(4)(5). Effects of mechanical wounding on Lupinus species have been earlier reported by Wink (6).…”
Section: Introductionmentioning
confidence: 86%
“…Induced resistance is defined as changes in plant chemistry or physiology with measurable effect on herbivore performance via behavior or biology (1). Results previously reported by our laboratory showed that different kinds of environmental stresses could affect secondary metabolite production, quinolizidine alkaloids among them (2)(3)(4)(5). Effects of mechanical wounding on Lupinus species have been earlier reported by Wink (6).…”
Section: Introductionmentioning
confidence: 86%
“…Changes in environmental conditions particularly in soil quality can trigger variations on secondary metabolites production. In a previous work , it was reported that C. album samples grown in Argentina in intensively cultivated soils produced larger amounts of nonpolar compounds such as long chain linear and branched hydrocarbons, fatty acid esters, and long chain alcohols and aldehydes. The aim of this work was to study the free radical scavenging ability and flavonoid contents in plant samples grown under the same conditions.…”
Section: Introductionmentioning
confidence: 98%
“…We have previously reported data related to the modulating effect of soil deterioration on secondary metabolites production by two widespread weed species, Chenopodium album and Senecio grisebachii. C. album samples grown in continuously cultivated (deteriorated) Argentinean Rolling Pampa soils have demonstrated to produce higher levels of long chain hydrocarbon derivatives (known to inhibit plant germination) than those grown in pristine soil (Leicach et al 2003). We have also demonstrated that the invasive weed S. grisebachii produced higher levels of toxic pyrrolizidine alkaloids in soils with higher deterioration degree.…”
Section: Abiotic Factorsmentioning
confidence: 76%